Effectiveness of multisensory stimulation in managing neuropsychiatric symptoms in older adults with major neurocognitive disorder: a systematic review. (August 2018) - Silva, Rosa; Abrunheiro, Sérgio; Cardoso, Daniela; Costa, Paulo; Couto, Filipa; Agrenha, Cátia; Apóstolo, João
ABSTRACT: Objective: The objective of the review was to synthesize the effectiveness of multisensory stimulation in managing neuropsychiatric symptoms (NPS) in older adults with major neurocognitive disorder (NCD). Introduction: Major neurocognitive disorder is characterized by changes in specific cognitive domains with a progressive deterioration in cognitive ability and capacity for independent living. Most older adults with this condition have one or more concomitant symptoms known as NPS. Evidence shows that nonpharmacological therapies have been effective in controlling these symptoms, with multisensory stimulation attracting further investigation. Inclusion criteria: The review considered studies on older adults aged 65 years or over with major NCD. The intervention of interest was multisensory stimulation, and the comparator was usual care (e.g. no occupational therapy, no cognitive training, and no art therapy, but with possible control of activities such as looking at photographs or doing quizzes), or another intervention (e.g. occupational therapy, cognitive training and art therapy). Primary outcomes were NPS (agitation, aggression, motor disturbances, mood liability, anxiety, apathy, night-time behaviour, eating disorders, delusion and hallucination). Secondary outcomes were quality of life, functional status in activities of daily living, cognitive status and caregiver burden. Experimental study designs were considered. Methods: A broad range of keywords and a three-step search strategy were used to identify potentially eligible published and unpublished studies from January 1990 to June 2016 in major healthcare-related online databases. Studies in English, Spanish and Portuguese were included. Two independent reviewers assessed the methodological quality of eight included studies using the Joanna Briggs Institute (JBI) Critical Appraisal Checklists for Randomized Controlled Trials and Quasi-Experimental Studies. Data were extracted using the standardized data extraction tool from the JBI System for the Unified Management, Assessment and Review of Information (JBI SUMARI) and included details about the interventions, populations, study methods and outcomes of interest. Significant differences were found between participants, interventions, outcome measures (clinical heterogeneity), and designs (methodological heterogeneity). For these reasons, a meta-analysis could not be performed. Therefore, the results have been described in a narrative format. Results: Eight studies (seven randomized controlled trials and one quasi-experimental study) were included, with a total sample of 238 participants (pre-intervention). Four studies confirmed the effectiveness of multisensory stimulation in domains such as physically nonaggressive behavior, verbally agitated behavior and agitation. However, these effects did not always persist in the long-term. Six studies showed poorly consistent results on the effects of multisensory stimulation in improving mood, with only one displaying significant effects. Similarly, despite poor results, two studies showed benefits concerning anxiety. Participants reported significantly decreased levels of anxiety over the course of the intervention, and this improvement persisted in the long-term. In regard to functional status in activities of daily living, two studies reported an improvement in the short-term. Moreover, the effectiveness in cognitive domains such as memory and attention to surroundings also showed inconsistent results across the seven studies that analyzed this outcome. Two studies reflected an improvement during the intervention, but also reported a gradual decline in the long-term. Only one study observed significantly better results during the intervention that persisted until the follow-up assessment. Apathy, night-time behavior, eating disorders, delusion and hallucination were NPS that were not explored in the studies that met the criteria to be included in this review. Conclusions: These findings suggest that multisensory stimulation could be an effective intervention for managing NPS in older adults with major NCD in a mild to severe stage, particularly for managing behavioral symptoms such as agitation. This research provides an indication of the likely effect of the multisensory stimulation on NPS such as agitation and anxiety, as well on cognitive status.